Harmonic compensation capability‐based coordinated control for hybrid wind farms under distorted grid voltage conditions. Issue 9 (18th April 2019) - Liu, Ruikuo; Yao, Jun; Guo, Lisha; Wang, Xiongfei; Blaabjerg, Frede
Abstract : This article presents a harmonic compensation capability‐based coordinated control strategy for a hybrid wind farm including doubly fed induction generator (DFIG)‐based and direct‐driven permanent‐magnet synchronous generator (PMSG)‐based wind turbines operation under distorted grid voltage conditions. First, the maximum harmonic current compensation capabilities of the DFIG and PMSG systems are analysed in detail when the grid voltage is harmonically distorted. Combining the maximum harmonic current compensation capabilities with the harmonic current requirements of different control targets, the controllable operating regions of each control target of the DFIG and PMSG systems during network voltage distortions are presented. Furthermore, the effects of the voltage total harmonic distortion (THD) and the system operating conditions on the controllable operating regions are analysed. Based on the analysis, the coordination strategy is proposed for a hybrid wind farm without communication equipment between the different wind power generators. The proposed strategy can improve the interoperability and the output power quality of the entire hybrid wind farm during grid‐voltage harmonic distortions. Finally, the effectiveness of the proposed coordination strategy for the hybrid wind farm is validated by simulation and experimental results.